Beans for nutrition: The future roles of common beans in healthy diets - Bonilla Cedrez, Camila; Schiek, Benjamin E.; Prager, Steven D. (Bioversity International and the International Center for Tropical Agriculture, 2021)
Beans play multiple roles in fostering healthy and nutritious diets. However, despite their importance, the inclusion of beans in diets is low, differing by country and regions. Increased bean consumption has the potential to improve intake of protein and key amino acids and increase access to essential micronutrients like iron and zinc that are not readily available in other affordable foods such as cereals.